# Question 2.1 Determine *(t)-h(1) where *(t) = te "tu(t) and h(t)=etu(t) by using the Fourier transform. (2 points) 22. Consider a LTI system for which the input x(!) and output y) are related by d'y().do(1) 487(0) 2u(). Determine the system output y(t) if the input is *(0) = reu(1). dr using the Fourier transform (3 points) 2.3 Consider a LTI system with impulse response h(t) = sin(4(1-1))/=(1-1). (5 points) 2.3.1 Determine the system output y() if the input is x(1) - cos(65+) using the Fourier transform (3 points) 2.3.2 Determine the system output y() if the input is x(t) = sin(4(1+1))/(t+1) us Fourier transform (2 points)

BMN6TO The Asker · Electrical Engineering

Transcribed Image Text: 2.1 Determine *(t)-h(1) where *(t) = te "tu(t) and h(t)=etu(t) by using the Fourier transform. (2 points) 22. Consider a LTI system for which the input x(!) and output y) are related by d'y().do(1) 487(0) 2u(). Determine the system output y(t) if the input is *(0) = reu(1). dr using the Fourier transform (3 points) 2.3 Consider a LTI system with impulse response h(t) = sin(4(1-1))/=(1-1). (5 points) 2.3.1 Determine the system output y() if the input is x(1) - cos(65+) using the Fourier transform (3 points) 2.3.2 Determine the system output y() if the input is x(t) = sin(4(1+1))/(t+1) us Fourier transform (2 points)
More
Transcribed Image Text: 2.1 Determine *(t)-h(1) where *(t) = te "tu(t) and h(t)=etu(t) by using the Fourier transform. (2 points) 22. Consider a LTI system for which the input x(!) and output y) are related by d'y().do(1) 487(0) 2u(). Determine the system output y(t) if the input is *(0) = reu(1). dr using the Fourier transform (3 points) 2.3 Consider a LTI system with impulse response h(t) = sin(4(1-1))/=(1-1). (5 points) 2.3.1 Determine the system output y() if the input is x(1) - cos(65+) using the Fourier transform (3 points) 2.3.2 Determine the system output y() if the input is x(t) = sin(4(1+1))/(t+1) us Fourier transform (2 points)
Community Answer
0UB1BU

Q. (2.2) Convsrting given q^(n) into loplace then will convest into fourier tranform:{:[s^(2)y(s)+6sy(s)+8y(s)=(2)/(s)],[y(s)=(2)/(s(s^(2)+6s+8))],[y(s)=(2)/(s(s^(2)+4s+2s+8))=(2)/(s[s(s+4)+2(s+4)])],[y(s)=(2)/(s(s+2)(s+4))]:}using partially fraction;y(s)=(1)/(4s)-(1)/(2(s+4)+ ... See the full answer